Veterinary Medicine in Tobolsk Governorate in Late 19th - Early 20th Centuries - D. V. Andriyanova; D. Yu. Fedotova (Научный диалог)
The article is devoted to the study of the peculiarities of the formation of veterinary medicine in the Tobolsk governorate in the late 19th - early 20th centuries. The authors use a representative source base of both published and unpublished materials from the collections of the Tobolsk State Archive. The conditions of organization of veterinary service in Siberia as a “remote area” are considered. It is noted that the development of veterinary medicine in the Tobolsk governorate was influenced by the opening of a veterinary and paramedic school. The novelty of the research is seen in the fact that for the first time in the national historiography the role of the provincial veterinary inspector in the formation of the Institute of veterinary service is considered. The activity of provincial veterinary inspectors is analyzed: P. Zolotarev, A. Ya. Lempert, L. S. Sumtsov and N. A. Kargapolov, who made a great contribution to the development of the veterinary service of the Tobolsk governorate in the studied period. It is shown that these doctors were highly educated and had an extensive experience in veterinary medicine. It is indicated that, despite all efforts and significant progress in the development of veterinary services, there were objective difficulties in this area, including difficult climatic conditions, long distances between settlements, the beginning of the First world war, etc.